Integrative identification of key genes governing Verticillium wilt resistance in Gossypium hirsutum using machine learning and WGCNA - Yufeng Lei; Jing Zhao; Siyuan Hou; Fufeng Xu; Chongbo Zhang; Dongchen Cai; Xiaolei Cao; Zhaoqun Yao; Sifeng Zhao (Frontiers in Plant Science)
IntroductionVerticillium wilt, caused by Verticillium dahliae, is one of the most devastating diseases affecting global cotton (Gossypium hirsutum) production. Given the limited effectiveness of chemical control measures and the polygenic nature of resistance, elucidating the key genetic determinants is imperative for the development of resistant cultivars. In this study, we aimed to dissect the temporal transcriptional dynamics and regulatory mechanisms underlying Gossypium hirsutum response to V. dahliae infection.MethodsWe employed a time-course RNA-Seq approach using the susceptible upland cotton cultivar Jimian 11 to profile transcriptomic responses in root and leaf tissues post-V. dahliae inoculation. Differentially expressed genes (DEGs) were identified, followed by weighted gene co-expression network analysis (WGCNA). To prioritize key candidate genes, we applied machine learning algorithms including LASSO, Random Forest, and Support Vector Machine (SVM).Results and discussionA robust set of core genes involved in pathogen recognition (GhRLP6), calcium signaling (GhCIPK6, GhCBP60A), hormone response, and secondary metabolism (GhF3’H) were identified. Our findings provide novel insights into the spatiotemporal regulation of immune responses in cotton and offer valuable candidate genes for molecular breeding of Verticillium wilt resistance.